"Profitability" vs. "Making It:" Causes and Consequences of Disembedding Beginning Farms' Finances. (18th June 2019) - Rissing, Andrea
Abstract: Efforts to recruit, train, and support beginning farmers often emphasize that mastering business finances is a key to farm success. Such efforts to inculcate business mentalities in new farmers are akin to farm‐level projects of economic disembedding. While many experts hold that isolating a farm's financial metrics reveals its viability, this article draws upon Polanyian economic understandings to argue that disembedding a farm's finances is fundamentally impossible and that a new farm's finances do not reliably indicate its longevity. Analysis of 12 Iowa cases where alternative farmers decided to quit within five years shows that not all profitable farms succeed. Rather, factors such as personal relationships, burnout, and dissatisfaction with rural life interact with a farm's finances to impact decision‐making in highly individual ways. Instead of reducing farm economics to farm finances, this article argues for a contextual understanding of financial considerations within social, historical, and relational elements.